(untitled) (International Journal of Advances in Pharmaceutics, 2026)
Fast dissolving oral films (FDOFs) have emerged as a promising patient-centric drug delivery system designed to overcome the limitations associated with conventional oral solid dosage forms, such as swallowing difficulty, delayed onset of action, and poor patient compliance. The present research work was aimed at the optimization and evaluation of fast dissolving oral films of Venlafaxine Hydrochloride, a serotonin–norepinephrine reuptake inhibitor widely used in the management of depressive and anxiety disorders. Fast dissolving oral films were prepared using the solvent casting method with hydrophilic film-forming polymers and suitable plasticizers. The prepared films were evaluated for physicomechanical properties including thickness, weight uniformity, folding endurance, tensile strength, surface pH, disintegration time, drug content uniformity, and in-vitro drug release. Optimization was carried out by varying polymer and plasticizer concentrations to achieve rapid disintegration and adequate mechanical strength. The optimized formulation demonstrated uniform drug distribution, satisfactory mechanical properties, rapid disintegration within seconds, and more than 95% drug release within a short duration, indicating fast availability of the drug. Stability studies conducted under accelerated conditions showed no significant changes in physical appearance, drug content, or dissolution behavior, confirming formulation stability. The study concludes that fast dissolving oral films of Venlafaxine Hydrochloride represent a safe, effective, and patient-friendly alternative to conventional oral dosage forms, with potential to enhance therapeutic efficacy, patient compliance, and quality of life.